SOME CONSIDERATIONS ON THE CONDUCT OF ARCHAEOLOGICAL RESEARCH AT THE NATIONAL UNIVERSITY OF UZBEKISTAN - Эргашев Ҳ. Ю. (TARIXIY TADQIQOTLAR, 2026)
During the years of independence, this brief scholarly work aims to analyze the scope and quality of the activities carried out by the Department of Archaeology of the National University of Uzbekistan in conducting archaeological research and presenting its results to the academic community. In addition, it serves, to a certain extent, to highlight the department’s contribution to the development of the field within the republic.